Distribución de tres especies del género Heleobia Stimpson, 1865 (Gastropoda, hydrobiidae) en el litoral argentino del Río de la Plata y arroyos afluentes - Darrigran, Gustavo Alberto (1995)
The distribution patterns of three species of Heleobia Stimpson, 1865 were analyzed. Two environments were considered: the argentine littoral of the Rio de la Plata and its affluent streams. Twentyseven localities were sampled: fourteen along the Rio de la Plata littoral and thirteen along its affluent streams. Heleobia piscium (Orbigny, 1835) and H. australis (Orbigny, 1835) were found only in the Rio de la Plata littoral. The relationships between the distribution of these two species and the salinity gradients of the Rio de la Plata are commented. H. parchappei (Orbigny, 1835) was found only in the studied streams. H. piscium is more tolerant to different ranges of salinity than the other species studied.